Applications Motor Credit Payment In PT BPR Universal - Risdianto Risdianto; Ire Puspa W, SKom, MMSI (Jurnal Sistem Informasi, 2006)
This explains the scientific writing about the design of application programs motor credit payment transactions using the programming language Visual Basic 6.0. In scientific writing database is used also by using the program Active Data Object (ADO) which has been integrated in visual basic 6.0 program itself. Consists of 4 tables of customers, collectors, credit and consumer installment.   At the end of the application programs of foreign exchange transactions will be applied to the PT. BPR Universal to facilitate in conducting motor credit payment transactions, such as creating reports.